(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Mother milk provides many health benefits for both mother and baby. Supporting breastfeeding by health workers has a beneficial effect on breastfeeding, especially during the baby's feeding period exclusively with mother milk. This study investigated the effect of education through cyberspace on continued breastfeeding in primiparous women. Methods: This experimental-classic study was performed on 65 primiparous women aged 28-32 weeks who were referred to Shahroud child birth preparation centers in 2018. Sampling was done randomly in two experimental and control groups. The experimental group received a training program based on continuous breastfeeding in 7 sessions, 45-60 minutes. The data were collected using a demographic and continuous breastfeeding questionnaire. The data were analyzed with SPSS21 using independent t-test, paired t-test and covariance test (P<0.05). Results: The mean and standard deviation of continuation of breastfeeding were 28.72±3.96 before intervention and 31.54±4.5 after intervention in the experimental group and 31.31±3.41 before intervention and 29.43±2.91 after intervention in the control group. Therefore, the duration of continued breastfeeding was longer in the experimental group compared to the control group after intervention. Conclusions: According to the results, education through cyberspace is recommended as an easy, safe, low cost and effective intervention for controlling and resolving lactating mothers' problems.